Proses Produksi Piring Porcelain Tipe KP24C Dengan Mesin Automatic Ceramic Machine (ACM) di PT. Kedaung Oriental Porcelain Industry (KOPIN) - Eko Aprianto Nugroho; Sandy Suryady; Ahmad Sutarno (Asosiasi Dosen Muda Indonesia, 2026)
Porcelain is a type of high-quality ceramic material known for its excellent physical and chemical properties. It is characterized by high density, very low water absorption (less than 0.5%), and good mechanical strength, making it ideal for household products such as plates. The main raw materials used in porcelain production include kaolin (white clay), feldspar, and quartz, which are processed through forming, drying, and firing stages at high temperatures around 1200–1400°C. In the production of KP24C type porcelain plates, materials such as clay, kaolin, silica sand, and feldspar are used. The process begins with the mixing stage, where materials are blended until homogeneous. Then, the filter press stage reduces the moisture content to 23%, resulting in a material called cake. This cake is further processed in a pugmill for homogenization. The forming stage uses an Automatic Ceramic Machine (ACM) for automatic shaping. The plates are then fired in a kiln to remove all moisture (0% water content). The next stage involves glazing to provide a glossy surface, followed by secondary drying in the finishing glossware process. The final stage is quality control, which includes visual inspection, color, gloss, dimensions, and shape assessments. Test results show a shrinkage percentage of approximately 28,21% after firing, indicating the success of the densification and drying process.